Mitochondrial DNA provides an insight into the mechanisms driving diversification in the ithomiine butterfly Hyposcada anchiala (Lepidoptera: Nymphalidae: Ithomiinae) - Alaine WHINNETT; Keith R. WILLMOTT; Andrew V.Z. BROWER; Fraser SIMPSON; Marie ZIMMERMANN; Gerardo LAMAS; James MALLET (European Journal of Entomology, 2005)
Geographic subspecies of several ithomiine butterflies on the lower east Andean slopes display a black and orange "melanic tiger" aposematic wing pattern that occurs from Colombia to Bolivia, while geographically adjacent lowland subspecies typically bear a coloured, "tiger" pattern. However, it is not clear whether subspecies with similar wing patterns in different regions have arisen through independent events of convergent adaptation, possibly through parapatric differentiation, or result from allopatric differentiation, as proposed by the refuge hypothesis. Here, we examine geographic patterns of divergence in the widespread and common ithomiine butterfly Hyposcada anchiala. We present phylogenetic hypotheses for 5 subspecies of H. anchiala, based on 1567 bp mitochondrial DNA. All topologies indicated that a single switch in mimetic pattern best explained the wing patterning of the H. anchiala studied here. This finding suggests that the subspecies of H. anchiala studied here result from at least two stages of differentiation, and is consistent with a single colonisation into a novel altitudinal zone coincident with a wing pattern switch, followed by subsequent divergence within, rather than across altitudinal zones. The subspecies divergences indicated diversifications were consistent with the Pleistocene. Furthermore, the lowland subspecies were more recently derived than the montane taxa, in contrast to predictions of the "Andean species pump" hypothesis.